Trade and sustainable fisheries - Ussif Rashid Sumaila (Asian Development Bank Institute (ADBI), 2017)
The ultimate goal of this contribution is to formulate fish trade policy recommendations that can be deployed to help achieve the relevant Sustainable Development Goals of the United Nations (SDGs). Even though all the 17 SDGs are relevant to the issues addressed in this contribution, I will focus on SDG14: Life under the water, and also SDG 1 (No poverty); 2 (Zero hunger); 3 (Gender equality); 4: (Reduced inequality); and 12 (Responsible consumption and production). Before I get to the recommendations, I will review the literature on the relationship between fish trade and sustainable fisheries; and discuss the potential promise (pros) and perils (costs) of fish trade. Policy recommendations for using fish trade to support the SDGs are provided under different headings that capture the main concerns highlighted in the literature when it comes to ensuring the sustainability of fisheries in general and those related to the impact of trade on fisheries sustainability in particular. The policy measures presented in this chapter have the potential to help ensure that trade in fish and fish products would support the implementation of the SDGs.
Keywords: G22; G27; G28; 330; Economics; Industry and trade